2016
DOI: 10.1016/j.ejso.2016.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Gastric GISTs: Analysis of c-Kit, PDGFRA and BRAF mutations in relation to prognosis and clinical pathological characteristics of patients – A GIRCG study

Abstract: Background: Gastric gastrointestinal stromal tumors (GISTs) represent a subgroup of GISTs with a better prognosis than those located in other areas. In this retrospective study we performed a molecular characterization of a large series of patients with gastric GISTs in relation to clinicalepathological characteristics and prognosis. Methods: DNA was extracted from paraffin-embedded sections from 221 gastric GIST patients submitted to surgery. Exons 9, 11, 13 and 17 of KIT, exons 12 and 18 of PDGFRA and exons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The major driving elements in GIST pathogenesis are linked with mutations in tyrosine kinase family (KIT) or platelet-derived growth factor (PDGFRA) gene [ 1 , 2 ]. Only a small proportion of GISTs appear to be associated with neither KIT or PDGFR sporadic mutations and are referred to as wild-type (WT) tumors [ 3 ]. GISTs most commonly arise from the fourth layer of the gastrointestinaltract wall (muscularis propria), and less often from the more superficial muscularis mucosa layer [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The major driving elements in GIST pathogenesis are linked with mutations in tyrosine kinase family (KIT) or platelet-derived growth factor (PDGFRA) gene [ 1 , 2 ]. Only a small proportion of GISTs appear to be associated with neither KIT or PDGFR sporadic mutations and are referred to as wild-type (WT) tumors [ 3 ]. GISTs most commonly arise from the fourth layer of the gastrointestinaltract wall (muscularis propria), and less often from the more superficial muscularis mucosa layer [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, the clinical model was used to predict the biological behaviors of GISTs (25), and genotypes have been shown to be closely related to certain clinical characteristics (26)(27)(28). However, the relationship between some clinical characteristics and the KIT 11 mutation remains controversial (26,27,29,30). Most of the previous studies showed that GISTs with the KIT exon 11 mutation usually had high percentages of mitotic count and/or poor prognosis (26,27,30).…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between some clinical characteristics and the KIT 11 mutation remains controversial (26,27,29,30). Most of the previous studies showed that GISTs with the KIT exon 11 mutation usually had high percentages of mitotic count and/or poor prognosis (26,27,30). The relationship between CA724 and GIST genotypes has not been reported until now.…”
Section: Discussionmentioning
confidence: 99%
“…The re-sults of published studies shows that KIT mutations in exon 11 can be linked with more aggressive tumor behavior 17,18 . Capelli et al 19 showed that the patients with gastric GIST who had the KIT mutations, were presented with worse pathological parameters, such as tumor necrosis, spindle cellularity, tumor size and mitotic index. Similar results were noted by Schaefer et al 20 .…”
Section: Discussionmentioning
confidence: 99%